2016
DOI: 10.1097/qai.0000000000001038
|View full text |Cite
|
Sign up to set email alerts
|

Male Partner Participation in Antenatal Clinic Services is Associated With Improved HIV-Free Survival Among Infants in Nairobi, Kenya: A Prospective Cohort Study

Abstract: Objective This prospective study investigated the relationship between male antenatal clinics (ANC) involvement and infant HIV-free survival. Methods From 2009-2013, HIV-infected pregnant women were enrolled from six antenatal clinics (ANC) in Nairobi, Kenya and followed with their infants until six weeks postpartum. Male partners were encouraged to attend antenatally through invitation letters. Males who failed to attend had questionnaires sent for self-completion postnatally. Multivariate regression was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
61
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 38 publications
(44 reference statements)
4
61
2
Order By: Relevance
“…23 Previous studies have demonstrated that male partner involvement is associated with improved uptake of services for the prevention of perinatal transmission 24 and HIV-free infant survival. 25, 26 Our results suggest that facilitated disclosure interventions may help women to maintain long-term treatment and viral suppression, particularly after delivery and the cessation of breastfeeding, when women remain in care for their own health.…”
Section: Discussionmentioning
confidence: 79%
“…23 Previous studies have demonstrated that male partner involvement is associated with improved uptake of services for the prevention of perinatal transmission 24 and HIV-free infant survival. 25, 26 Our results suggest that facilitated disclosure interventions may help women to maintain long-term treatment and viral suppression, particularly after delivery and the cessation of breastfeeding, when women remain in care for their own health.…”
Section: Discussionmentioning
confidence: 79%
“…Despite advances in HIV prevention of mother‐to‐child transmission (PMTCT) in sub‐Saharan Africa (SSA), pregnant and postpartum women face a high risk of HIV acquisition from infected male partners and subsequent mother‐to‐child transmission . Similarly, many HIV‐infected women have male partners who are also HIV‐infected and do not know their HIV status . Engaging male partners of pregnant and postpartum women in HIV testing can be a first key step towards improved health outcomes for HIV‐positive or HIV‐negative women, their male partners, and their infants, including better uptake of and adherence to antiretroviral treatment and reduced HIV‐related morbidity and mortality .…”
Section: Introductionmentioning
confidence: 99%
“…Several strategies, such as partner notification and community invitations have been effective for increasing cHCT and could have important implications if brought to scale. [39][40][41] Such efforts would have benefits on reduced HIV incidence and on reaching global HIV targets, including the 90-90-90 goals and elimination of mother-to-child transmission [42][43][44] Assessing the impact of HCT on HIV acquisition is methodologically challenging. First, all assessments of HIV acquisition require large cohorts followed for long periods with low, nondifferential loss to follow-up.…”
Section: Discussionmentioning
confidence: 99%